Pediatric Liver Disease Patients and Secondary Glycosylation Abnormalities - Bogdańska, Anna; Lipiński, Patryk; Szymańska-Rożek, Paulina; Jankowska, Irena; Socha, Piotr; Tylki-Szymańska, Anna (Frontiers in Pediatrics, 2021)
Background: Isoelectric focusing (IEF) of serum transferrin (Tf) is still the method of choice for diagnosis of congenital disorders of glycosylation (CDG). An abnormal glycosylation is also a known phenomenon in adult liver disease patients. However, there are no reports of this phenomenon in children. The aim of this study was to characterize glycosylation disturbances in pediatric patients with primary liver disease. Material and methods: Between 1995-2019, circa 2,000 serum Tf isoform analyses have been performed in children with primary liver diseases; some of them underwent subsequent analyses. We enrolled in this study 19 patients who developed an acute liver injury (ALI)/failure (ALF) or exhibited a chronic liver disease (CLD) and were evaluated and listed for liver transplantation (LTx) or had just undergone this procedure, and secondary abnormal serum Tf isoform profile. Results: Among 12 patients with ALI/ALF, 10 had an increased percentage of asialo-, monosialo- and disialo-Tf isoforms. All patients with CLD had an increased percentage of asialo- and monosialo-Tf isoform. Two patients diagnosed with recurrent ALF had very specific serum Tf profile with a huge increase in the asialo- and monosialo-Tf isoform. On follow-up analyses (available in some patients), serum Tf IEF profile normalized in parallel to normalization of liver function tests, spontaneously or during treatment, including glucocorticosteroids in AIH, LTx in CLD. Conclusions: All paediatric patients with primary liver disease had increased asialo-Tf as well as monosialo-Tf isoforms. None of them had elevated percentage of trisialo-Tf isoform.